Sleep and Breathing After Nusinersen Therapy in a Child With Spinal Muscular Atrophy. Issue 2 (December 2020) - Kouri, Ioanna; Demirel, Nadir; Haile, Dawit T.; Selcen, Duygu; Kotagal, Suresh
Abstract: Background: Spinal muscular atrophy (SMA) type 3 is an autosomal recessive neurological disorder associated with a deletion/mutation in the survival motor neuron gene, with gradually progressive degeneration of the motor neurons of the spinal cord and brainstem, which causes muscle weakness responsible for impairment of swallowing, breathing, and mobility. Report of case: We report an 11-year-old girl with SMA type 3 with moderate to severe obstructive sleep apnea (OSA) syndrome refractory to adenotonsillectomy and noninvasive ventilatory support. She was started on nusinersen, which is a novel disease modifying therapy for SMA. This new treatment led to improvement of the OSA in a short period, likely from better respiratory muscle function. Conclusions: The improvement in OSA supports the role of nusinersen in sleep-related upper respiratory muscle function in SMA type 3.